Experiences among firefighters and police officers of responding to out-of-hospital cardiac arrest in a dual dispatch programme in Sweden: an interview study - Jacob Hollenberg; Per Nordberg; Ingela Hasselqvist-Ax; Leif Svensson; Eva Joelsson-Alm (BMJ Open)
Objectives The objective of this study was to explore firefighters’ and police officers’ experiences of responding to out-of-hospital cardiac arrest (OHCA) in a dual dispatch programme.Design A qualitative interview study with semi-structured, open-ended questions where critical incident technique (CIT) was used to collect recalled cardiac arrest situations from the participants’ narratives. The interviews where transcribed verbatim and analysed with inductive content analysis.Setting The County of Stockholm, Sweden.Participants Police officers (n=10) and firefighters (n=12) participating in a dual dispatch programme with emergency medical services in case of suspected OHCA of cardiac or non-cardiac origin.Results Analysis of 60 critical incidents was performed resulting in three consecutive time sequences (preparedness, managing the scene and the aftermath) with related categories, where first responders described the complexity of the cardiac arrest situation. Detailed information about the case and the location was crucial for the preparedness, and information deficits created stress, frustration and incorrect perceptions about the victim. The technical challenges of performing cardiopulmonary resuscitation and managing the airway was prominent and the need of regular team training and education in first aid was highlighted.Conclusions Participating in dual dispatch in case of suspected OHCA was described as a complex technical and emotional process by first responders. Providing case discussions and opportunities to give, and receive feedback about the case is a main task for the leadership in the organisations to diminish stress among personnel and to improve future OHCA missions.